Socio-demographic profile of the members of the 1986 constitutional commission - Paez-Hidalgo, Ma. Victoria; Israel, Gina C.; Saguil, Dan A. (1987)
A survey of the 1986 Constitutional Commission's socio-demographic profile reveals that its membership does not reflect the composition of the entire Filipino nation. Socio-demographic variables such as age, political/organizational affiliation, income, profession, occupation, ethnicity, religion, educational background and ownership of properties were correlated with the commissioners' attitude, actual behavior and positions on certain vital policy issues such as the US bases, national patrimony, national language and land reform. The commissioners themselves admit that the constitution they framed is imperfect but it is the best they could produce given their limited time and resources.
Keywords: Philippine Constitutional Commission -- 1986; Constitutional Commission -- Selection and appointment